1994
DOI: 10.1161/01.cir.90.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias in the acute and chronic phases after acute myocardial infarction. Effect of intervention with captopril.

Abstract: Dilation of the left ventricle and myocardial ischemia predict VA during both the acute and chronic phases after MI. In post-MI patients with LV dysfunction, captopril has a beneficial effect on both the number of complex VAs as well as the number of patients who develop VA during the chronic phase. This is in all probability mediated through effects on both LV remodeling, LV function, and myocardial ischemia in patients who are exposed to an increased risk of undergoing progressive dilation of the left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…Remodeling is linked to heart failure progression and is associated with poor prognosis following myocardial infarction. Ventricular dilation following myocardial infarction is an important predictor of mortality [6] and adverse cardiac events [7], including the development of heart failure and ventricular arrhythmias [8], [9]. The extent of adverse remodeling depends on the size of the infarct but is also directly affected by the pathologic and structural changes associated with infarct healing.…”
Section: Introductionmentioning
confidence: 99%
“…Remodeling is linked to heart failure progression and is associated with poor prognosis following myocardial infarction. Ventricular dilation following myocardial infarction is an important predictor of mortality [6] and adverse cardiac events [7], including the development of heart failure and ventricular arrhythmias [8], [9]. The extent of adverse remodeling depends on the size of the infarct but is also directly affected by the pathologic and structural changes associated with infarct healing.…”
Section: Introductionmentioning
confidence: 99%
“…6, lead to worse arrhythmic outcomes because of increased wall strain and stress, which in turn trigger stretch-activated ion channels. 23,24 Also, LV remodeling is correlated with infarct size, 25,26 and so are arrhythmic events. 27 The increased wall stress caused by LV dilation and thinning also elicit compensatory responses, and when these responses are inadequate, a vicious cycle of further dilation ensues, and the heart eventually fails.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have demonstrated that angiotensin-converting enzyme (ACE) inhibitors prevent ventricular arrhythmias following acute or chronic myocardial ischemia [1, 2, 3, 4, 5, 6]. This antiarrhythmic effect was generally considered to be the result of reduced severity of ischemia and the subsequent injury to the myocardium [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies have indicated that other factors, such as the remodelling of the left ventricle [1], the suppressed release of endothelin-1 [2]and noradrenaline [3], may be also responsible for the antiarrhythmic effect of ACE inhibitors. In patients with acute or chronic myocardial ischemia, the attenuation of sympathetic activation [4]and left ventricular dilatation [5]is particularly important in mediating the antiarrhythmic effect of ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%